The Role of the Secondary Schools Institutions in Al-Rass in Developing the Creativity of their Students - Elsheikh, Elsheikh Elgaili (Journal of Educational and Psychological Sciences, 2022)
The aim of the present research is to investigate the role of the secondary schools Institutions in improving the creativity of their students from the students’ ’point of view’. The descriptive analytic method is used in this research. The study tool is a questionnaire of five fields distributed to a sample of study consisted of (386) male and female students at the second and third secondary levels in Al-Rass. The results showed that the general average of students’ ratings for the practice of secondary schools for their role in developing creativity was (3.22 out of 5), i.e. with a general assessment of the role (average). At the level of the studied fields, the school environment field had the highest average (3.47), followed by the teacher’s field with an average of (3.43, both with a role rating (high). The field of the community and the family ranked third with an average of (3.19), and the school curriculum came in the fourth place with an average of (3.08), and finally the field of school administration showed an average of (2.89), all with a general rating (average). The results also found that there were no statistically significant differences at the level (α ≤ 0.05) between the averages of the estimates of the study sample on the role of secondary education schools in developing creativity among its students. This is attributed to the two variables: (Gender, and class). There was no statistically significant relationship at the level (α ≤ 0.05) between the level of the estimates of the research sample and the students’ standard of living. Based on the results, the researcher recommends preparing the school environment for creativity development, including creativity development strategies in the teacher preparation programs and curricula, and urging teachers to use teaching strategies that enable them to develop creativity skills among their students, and to know and resolve obstacles to creative thinking. In addition to make proposals for complementary studies on this subject.